Pode a Física ser um bom árbitro para questões epistemológicas? - Ponczek, Roberto Leon (2009)
Many  researchers  have  been  thinking  on  the  importance of Epistemology for the Physics understanding, and on its teaching, but the  reciprocal is not true. Very few attempts were  made concerning the possibility of Physics to  contribute for a good understanding of Epistemology. We intend to show how Physics can be useful to arbitrate about an epistemological secular subject concerning  the origin of the knowledge: if it is reached by  the senses, as it defends the Empiricism, or by reason, as it defends the Rationalism. With some simple examples extracted from Newtonian mechanics, we will show that correlations exist  among facts without causality and vice-versa  it  can exist a hidden causality linking facts without correlations, which weakens the orthodox empiricism position concerning the  origin of the knowledge, opening new and strong arguments against a inductive-empiricist teaching, as proposed by some known Physics textbooks.